Zadacha Kuznecov Predely 10-24

Материал из PlusPi
Перейти к: навигация, поиск

Условие задачи

Вычислить предел функции:

<math>\lim_{x\to 0} \frac{\sqrt[3]{8+3x-x^2}-2}{\sqrt[3]{x^2+x^3}}</math>

Решение

<math>\lim_{x\to 0} \frac{\sqrt[3]{8+3x-x^2}-2}{\sqrt[3]{x^2+x^3}} = </math>
<math> = \lim_{x\to 0} \frac{\left(\sqrt[3]{8+3x-x^2}-2\right)\left(\sqrt[3]{\left(8+3x-x^2\right)^2}+2\sqrt[3]{8+3x-x^2}+4\right)}{\left(\sqrt[3]{x^2+x^3}\right)\left(\sqrt[3]{\left(8+3x-x^2\right)^2}+2\sqrt[3]{8+3x-x^2}+4\right)} = </math>
<math> = \lim_{x\to 0} \frac{8+3x-x^2-8}{\sqrt[3]{x^2}\sqrt[3]{1+x}\left(\sqrt[3]{\left(8+3x-x^2\right)^2}+2\sqrt[3]{8+3x-x^2}+4\right)} = </math>
<math> = \lim_{x\to 0} \frac{x(3-x)}{\sqrt[3]{x^2}\sqrt[3]{1+x}\left(\sqrt[3]{\left(8+3x-x^2\right)^2}+2\sqrt[3]{8+3x-x^2}+4\right)} = </math>
<math> = \lim_{x\to 0} \frac{\sqrt[3]{x}(3-x)}{\sqrt[3]{1+x}\left(\sqrt[3]{\left(8+3x-x^2\right)^2}+2\sqrt[3]{8+3x-x^2}+4\right)} = </math>
<math> = \frac{\sqrt[3]{0}(3-0)}{\sqrt[3]{1+0}\left(\sqrt[3]{\left(8+3\cdot 0-0^2\right)^2}+2\sqrt[3]{8+3\cdot 0-0^2}+4\right)} = </math>
<math> = \frac{0}{1\cdot \left(\sqrt[3]{8^2}+2\sqrt[3]{8}+4\right)} = 0</math>